The Relationship Between Abusive Experiences and Staff Controls in Juvenile Correctional Facilities: The Mediating Effects of Externalizing Behavior - Hodge, Ashleigh I. (Criminal justice and behavior, 2017)
To maintain safety and order, some correctional settings permit the use of controls on youth in response to behavioral problems; however, use of controls may exacerbate trauma symptoms that many youth bring to the carceral experience. Data from the Survey of Youth in Residential Placement are used in this study (N = 7,073). Structural equation modeling was used to test three hypotheses: (a) youth with a history of physical, sexual, and emotional abuse report greater use of staff controls; (b) externalizing behaviors partially mediate this relationship; and (c) externalizing behavior and staff controls are mutually reinforcing. Findings suggest that youth with physical and sexual abuse histories experience greater staff controls. Externalizing behavior was a partial mediator and a reciprocal product of staff controls. Such findings warrant caution for institutional policies and staff practices that promote the use of control, and instead call for the use of trauma-informed responses to misbehavior.